STUDENT ENGAGEMENT AND MATH TEACHERS SUPPORT - Tahani Salman Alrajeh; Beth Winfrey Shindel (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
This study aimed to investigate the factors that influence student engagement in mathematics classes. It explored the relationship among emotional, organizational, and instructional support and the impacts of characteristics of teacher, such as years of experience, and sexual orientation, on student engagement. Data were taken from the Consortium for Political and Social Research. The study was involved mathematics teachers and encompassed three years of data collection and observation. Data were collected first hand through classroom observations and student–teacher surveys. In this study, ANOVA, t-test, and partial correlation were employed to evaluate the relationships among the study variables based on participants’ responses. The relationship between student engagement and instructional support weakened after controlling for emotional and organizational support. However, instructional support continued to significantly influence student engagement. In addition, results showed a significant difference in student engagement attributed to the teacher’s gender. Results revealed the interaction between gender and years of experience significantly influenced student engagement, which was in favor of female teachers.